'The Story Continues …' Schelling and Rosenzweig on narrative philosophy. Issue 1 (15th March 2019) - Bielik-Robson, Agata
ABSTRACT: In my essay, I analyze Schelling's and Rosenzweig's commitment to the narrative philosophy as a unique method of telling a philosophical story. I want to understand what such "philosophical story" means and how it differs from the conceptual approach, here represented by Hegel. I also want to see how it connects with Schelling's another project continued by Rosenzweig, of doing "positive philosophy": in what way does positivity imply narrativity? Is this a necessary implication? And, last but not least, I want to explore the theological dimension of the narrative project. I perceive Schelling's, and then Rosenzweig's goal as an attempt to oppose Hegel's double manoeuvre of sublation – of temporal contingency and religion – by returning to the narrative which recovers the actuality of both elements and sees the necessary connection between them. The living experience of history is strictly linked to the religious stories telling the life of the "living God, " who is emphatically not the "God of the system." Theosophy and its narrative way of creating a suspense and then inscribing it into a metaphysical drama which plays itself out on the arena of history reveals the deep connection between living historical temporality and religious imagery.